BAROMEMBRANE TECHNOLOGIES AS A PROSPECTIVE ALTERNATIVE TO VACUUM EVAPORATION IN THE DRY MILK PRODUCTION - A. G. Kruchinin; E. E. Illarionova; A. V. Bigaeva; S. N. Turovskaya (Academic Scientific Journal of Chemistry, 2021)
In the dairy industry, in recent years, baromembrane technologies (microfiltration, ultrafiltration, nanofiltration, reverse osmosis) have become increasingly widespread, which make it possible to obtain milk raw materials that are safe from a microbiological point of view and to standardize the protein mass fraction, concentration and fractionation of milk constituents. These filtration methods are definitely an alternative to traditional manufacturing processes. They are integrated into many production steps for a wide range of whole milk products, cottage cheese, cheese, etc. Among dry dairy products, milk powder occupies a leading position in terms of use for processing in powdered or reconstituted form in almost all sectors of the food industry due to its high nutritional value, transportability, long shelf life, etc. In this regard, from quality and safety, and also the technological properties of milk powder certainly depend on the final product quality. Improving the organoleptic, physicochemical, sanitary and hygienic indicators of milk powder and directionally forming its basic technological properties (thermal stability, cheese suitability, solubility), it is possible to design its food and functional technological profile, using baromembrane installations in the process of obtaining milk powder. Based on the study of specialized scientific and technical literature, the article presents an analysis and systematization of information on the influence of baromembrane methods, integrated into the technological chain of obtaining milk powder, on its quality and functional and technological properties